Assessing the impact of residual film on agriculture: A meta-analysis of soil moisture, salinity, and crop yield - Jingrun Wang; Hongguang Liu; Reaihan E; Ping Gong; Pengfei Li; Changkun Yang; Ling Li; Yibin Xu; Jianshu Dong; Yong Guo (Ecotoxicology and Environmental Safety)
Residual films (RFs) disrupt the normal migration and distribution of water, salts and nutrients in soil, posing a significant threat to the sustainable development of agriculture and food security. The effect complexity of RF on soil water-salt distribution and crop growth result in conflicting findings in previous studies. Systematic and quantitative exploration of RF thresholds is of great significanse. Focusing on the influence of RF on agriculture, this study conducted a meta-analysis of 44 peer-reviewed studies using 1514 soil moisture data points, 568 soil salt data points, and 312 yield data points. The results showed: RF reduced the soil moisture by 2.62 %, decreased the crop yield by 11.72 %, and increased the soil salinity by 4.09 %. These adverse effects were exacerbated in environments with an average annual evapotranspiration (AAE) > 1800 mm, average annual precipitation (AAP) < 500 mm, and average annual temperature (AAT) < 10°C. Although the degradable film (DF) outperformed the ordinary ones, no significant difference was observed between the RFs of varying thicknesses (p > 0.05). RF levels between 0 and 225 kg·ha−1 had no significant effect on transport of water, salt or crop yield, but levels above 225 kg·ha−1 significantly reduced crop yield (p < 0.05). The yield reduction in cotton (-14.13 %) was more pronounced than that in grain crops (-11.3 %), and the negative effects improved with crop growth. The RF thresholds for yield reduction were 300 kg·ha−1 for grain crops and 450 kg·ha−1 for cotton. This study offers scientific guidance for effective RF management and optimization in agricultural production.